Effect of isomaltooligosaccharide and gentiooligosaccharide on the growth and fatty acid profile of Lactobacillus plantarum - Soto, Carmen (Electronic Journal of Biotechnology, 2013)
Background: Lactobacillus sp. are probiotic microorganisms, and some of them are able to produce conjugated linoleic acid (CLA) via the bio-hydrogenation of linoleic acid (LA). Both CLA and LA are polyunsaturated fatty acids commonly used in the prevention and control of cardiovascular disease, high cholesterol, and cancer, among other ailments. The carbon source is one variable that can affect the growth and characteristics of these bacteria. Molecules called prebiotics are known to benefit human health by stimulating the growth and activity of probiotic bacteria present in the intestinal microflora. The aim of this study was to evaluate how different oligosaccharides affect the growth and fatty acid profile of Lactobacillus plantarum (NRRL - B4496). L. plantarum cultivation was performed in Man-Rogosa-Sharpe (MRS) medium, and the original carbon source (glucose) in this medium was partially or totally replaced by an oligosaccharide (isomaltooligosaccharide (IMO) or gentiooligosaccharide (GTO)). Then, the biomass concentration and fatty acid profile were determined using spectrophotometry and gas chromatography, respectively. Results: When 50% of the glucose in the MRS medium was replaced with IMO, the maximum growth was 2.6 g/L at 37ºC. Under the same culture conditions, the incorporation of GTO only produced 2 g/L of biomass. At 45ºC, the growth of the bacterial culture was lower than that observed at 37ºC, reaching only 0.4 g/L. When cultivated at 37ºC in a mixture of glucose and GTO (1:1), CLA (34%, c9t11) was obtained from cells of L. plantarum. However, when the cultivation was performed at 45ºC, CLA was not obtained. When IMO was used, differences in CLA content were not observed between L. plantarum cultivated with glucose or with IMO present; however, vaccenic acid was produced. Conclusions: Lactobacillus plantarum grow well when a mixture of IMO and glucose is used as the carbon source. However, this mixture does not improve the CLA content, most likely due to high enzymatic activity that promotes the conversion of CLA to vaccenic acid. Additionally, GTO is likely less readily metabolized by this strain. Thus, the enzymatic activity is likely lower and less CLA is converted to vaccenic acid, resulting in an accumulation of CLA.